Effect of Combined Training on Body Image, Body Composition and Functional Capacity in Patients with Breast Cancer: Controlled Clinical Trial - Reis, Andréa Dias; Pereira, Paula Tâmara Vieira Teixeira; Filha, Jurema Gonçalves Lopes Castro; Rodrigues, Evelyn Feitosa; Laranjeira, Isadora Pinheiro; Ramallo, Bianca Trovello; Castro, Marcela Rodrigues de; Rossi, Fabrício Eduardo; Júnior, Ismael Forte Freitas; Garcia, João Batista Santos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective: Evaluate the effect of combined training on body image (BI), body composition and functional capacity in patients with breast cancer. As also the relationship of BI with body composition and functional capacity.Methods: This was a Controlled Clinical Trial study, this study including 26 patients with breast cancer (30 to 59 years). The training group (n = 13) underwent 12 weeks of training, including three 60-min sessions of aerobic exercise and resistance training, and two sessions of flexibility training per week; each flexibility exercise lasted 20s. The Control Group (n = 13) received only the standard hospital treatment. Participants were evaluated at baseline and after 12 weeks. BI (primary outcomes) was assessed using the Body Image After Breast Cancer Questionnaire; Body composition was estimated with the indicators: Body mass index; Weight, Waist hip Ratio; Waist height ratio; Conicity index; Reciprocal ponderal index; Percentage of fat; Circumference of the abdomen and waist; Functional capacity by cardiorespiratory fitness (cycle ergometer) and strength (manual dynamometer). The statistic was performed in the Biostatistics and Stata 14.0 (α = 5%).Results: The patients in the training group showed a reduction in the limitation dimension (p = 0.036) on BI, However, an increase in waist circumference was observed in both groups. In addition an increase in VO2max (p < 0.001) and strength in the right (p = 0.005) and left arms (p = 0.033).Conclusion: Combined training demonstrates to be an effective and non-pharmacological strategy to patients with breast cancer, with improvement on BI and functional capacity, changing related variables negatively when there is no physical training.
Keywords: Breast neoplasms; Health; Exercise; Women